Essays on the use of payment instruments - Silva, Vânia Gomes de Carvalho Gramaça da (2017)
The use of non-cash payment instruments in European Union (EU) countries changed quite noticeably in the past years. Electronic payment instruments usage grew, while paper-based payments declined. The objective of this thesis, comprised by three essays, is to provide empirical evidence of the impact on the use of cheques, bank cards, and credit transfers of a selected set of specific measures. As cheques are still a relevant question of concern for some countries due to their considerable social costs and risks, the first essay analyses the determinants of cheque usage in the EU, with data for the period 2000-2012. The study focuses on the effects of the application of fees in a framework where unfunded cheques are considered as an autonomous type of crime in some countries. The second essay examines the impact on cards usage of the adoption of the EMV (Europay, MasterCard and Visa) standard in the EU between 2006 and 2011. This technology protects information more effectively than magnetic stripes and aims to reduce fraud at the point-of-sale. Finally, the third essay investigates the effect of the implementation process of the Single Euro Payments Area (SEPA) – a project that intends to increase integration in retail payments – on credit transfers usage in euro area countries from 2008 to 2013. The results obtained suggest that: (i) the existence of fees influences negatively cheque usage, even when there are legal elements that increase security; (ii) the progress in the adoption of EMV technology had a positive effect in the use of cards; and (iii) the evolution in the migration to SEPA formats had a positive impact on the share of credit transfer payments; Ensaios sobre a utilização de instrumentos de pagamento Resumo: A utilização de instrumentos de pagamento que não o numerário na União Europeia (UE) registou significativas alterações nos últimos anos. O uso de instrumentos eletrónicos aumentou e os pagamentos assentes em papel reduziram-se. O objetivo desta tese, composta por três ensaios, é fornecer evidência empírica do impacto de um conjunto de medidas na utilização de cheques, cartões bancários e transferências a crédito. Dado que os cheques são ainda uma preocupação em alguns países atendendo aos custos sociais e riscos associados, o primeiro ensaio analisa os determinantes da utilização de cheques na UE, com dados para o período 2000-2012. O estudo centra-se nos efeitos da imposição de encargos num contexto em que a emissão de cheques sem provisão é considerada crime em alguns países. O segundo ensaio examina o impacto na utilização de cartões da adoção, entre 2006 e 2011, do padrão EMV (Europay, MasterCard e Visa) na UE. Esta tecnologia protege a informação de forma mais eficaz que as bandas magnéticas e visa reduzir a fraude nos pontos de venda físicos. Finalmente, o terceiro ensaio investiga o efeito da implementação da Área Única de Pagamentos em Euros (SEPA) – um projeto que visa impulsionar a integração nos pagamentos de retalho – na utilização de transferências a crédito nos países da área do euro entre 2008 e 2013. Os resultados obtidos sugerem que: (i) a existência de encargos influencia negativamente a utilização de cheques, mesmo quando existem fatores legais que aumentam a segurança; (ii) o progresso na adoção da tecnologia EMV teve um efeito positivo na utilização de cartões; e (iii) a evolução na migração para os formatos SEPA gerou um impacto positivo na proporção de pagamentos com transferências a crédito.